Contrasts and similarities in economic performance of migrant entrepreneurs - Mediha Sahin; Peter Nijkamp; Soushi Suzuki (IZA Journal of Migration, 2014)
In recent years, migrant entrepreneurs have come to occupy a prominent place in the SME sector in many cities in developed countries, with varying degrees of success. The concept of migrant entrepreneurship suggests a homogeneous set of actors, but it remains to be seen whether differences in cultural and ethnic backgrounds, in education, in age and gender, and in motivational profiles lead to contrasting business outcomes. The present paper aims to identify and compare differences in the economic performance of individual migrant business firms on the basis of a quantitative assessment of the drivers of their efficiency profiles. In this context, we will address in particular the drivers and barriers for the heterogeneous business strategies of specific classes of migrant entrepreneurs. After the use of a multivariate statistical analysis, a modern operational approach-originating from organizational theory-that aims to make a comparative study of quantitative efficiency differences between individual decision-making units (DMUs), viz. Data Envelopment Analysis (DEA) is employed. DEA is used here to assess relative performance differences between distinct categories of migrant entrepreneurs in the city of Amsterdam. A wealth of relevant data has been collected by systematic, personally-supervised interviews and questionnaires, and these contain a variety of efficiency-oriented indicators, on both the input and the output side. Several additional analyses - using multivariate cross-analysis methods - are also carried out to test the robustness of our findings by, inter alia, investigating the influence of specific socio-cultural ethnic groups, levels of education, first-and second-generation migrants, and age. Finally, the paper offers some lessons on entrepreneurship strategies.
Keywords: R10; O15; L26; 330; Data envelopment analysis; Migrant entrepreneurship; Efficiency performance